Religions of the United States in practice. - McDannell, Colleen (Princeton readings in religions., 2001)
Religions of the United States in Practice is a rich anthology of primary sources with accompanying essays that examines religious behavior in America. From praying in an early American synagogue to performing Mormon healing rituals to debating cremation, Volume 1 explores faith through action from Colonial times through the nineteenth century. The documents and essays consider the religious practices of average people--praying, singing, healing, teaching, imagining, and persuading. Some documents are formal liturgies while other texts describe more spontaneous religious actions. Because religious practices also take place in the imagination, dreams, visions, and fictional accounts are also included. Accompanying each primary document is an essay that sets the religious practice in its historical and theological context--making this volume ideal for classroom use and accessible to any reader. The introductory essays explain the various meanings of religious practices as lived out in churches and synagogues, in parlors and fields, beside rivers, on lecture platforms, and in the streets. Religions of the United States in Practice offers a sampling of religious perspectives in order to approximate the living texture of popular religious thought and practice in the United States. The history of religion in America is more than the story of institutions and famous people. This anthology presents a more nuanced story composed of the everyday actions and thoughts of lay men and women.